2019
DOI: 10.1017/jea.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Reputation and Compliance With International Human Rights Law: Experimental Evidence From the Us and South Korea

Abstract: Past studies suggest that domestic public support for compliance with international human rights law can constrain governments to comply with human rights law. But the question remains: Why does the public care about compliance? Using a series of survey experiments in South Korea and the United States, this study finds that constituents are concerned about compliance in one issue area—such as human rights—because they believe it will affect the country's reputation in other domains of international law. Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, compliance and trust are highly related (Braithwaite and Makkai 1994;Faizal et al 2017;Wong and Jensen 2020). Thus, compliance affects international and domestic reputation, partnerships, and competitiveness (Castelfranchi et al 1998;Kaminski and Robu 2016;Heidinger and Gatzert 2018;Kim 2019). In contrast, Ayadi et al (2016) indicated that specific regulatory (Basel Committee on Banking Supervision 2013) compliance has no association with bank efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compliance and trust are highly related (Braithwaite and Makkai 1994;Faizal et al 2017;Wong and Jensen 2020). Thus, compliance affects international and domestic reputation, partnerships, and competitiveness (Castelfranchi et al 1998;Kaminski and Robu 2016;Heidinger and Gatzert 2018;Kim 2019). In contrast, Ayadi et al (2016) indicated that specific regulatory (Basel Committee on Banking Supervision 2013) compliance has no association with bank efficiency.…”
Section: Introductionmentioning
confidence: 99%